Raf kinase inhibitor protein expression combined with peritoneal involvement and lymphovascular invasion predicts prognosis in Dukes' B colorectal cancer patients. Issue 3 (22nd January 2013) - Doyle, Brendan; Hagan, Suzanne; Al‐Mulla, Fahd; Scott, Lucy; Harden, Sharon; Paul, Jim; Mulcahy, Hugh; Murray, Graeme I; Sheahan, Kieran; O'Sullivan, Jacintha; Kolch, Walter
<x xml:space="preserve">Abstract</x> Aims There is controversy regarding the use of adjuvant therapy in patients with Dukes' B colorectal cancer (CRC). New markers, identifying high‐risk Dukes' B patients, are needed. Here, we examine the utility of Raf kinase inhibitor protein (RKIP) as such a marker and promoter methylation as a mechanism of RKIP down‐regulation. Methods and results We used a tissue microarray of 220 patients with Dukes' B CRC to examine the effect of RKIP expression on survival. Pyrosequencing was used to assess RKIP promoter methylation status. RKIP expression correlated inversely with disease‐specific survival in this cohort. In multivariate analysis, RKIP was found to be an independent prognostic indicator, along with peritoneal invasion and lymphovascular invasion (LVI). RKIP promoter hypermethylation was seen in only one of 29 tumours analysed by pyrosequencing. Conclusions Raf kinase inhibitor protein, peritoneal invasion and LVI provide independent prognostic information in this cohort of Dukes' B CRC patients. This demonstrates the potential utility of RKIP in identifying 'high‐risk' Dukes' B patients. It is this high‐risk group which is most likely to benefit from close postoperative monitoring and may derive the most benefit from adjuvant therapy.